Edukasi Konten Digital terhadap Anak Usia Dini di TK Negeri 3 Suryoputran Kota Yogyakarta - Dyaloka Puspita Ningrum (Jurnal Surya Masyarakat, 2023)
According to the Hootsuite We Are Social report, internet use in Indonesia continues to increase and is higher than the total population. Pierre Levy's perspective with two approaches, namely: social interaction and social integration is also able to show changes in behavior as well as shifts in public activity as a form of adaptation in the current era of disruption. The existence of the internet is like a double-edged sword, especially for groups of children at an early age who are very vulnerable to being exposed to negatively charged information and content, even though this condition has also been regulated in the Information and Electronic Transactions Law / UU ITE. This Community Service Activity is located at TK Negeri 3 Suryoputran Yogyakarta City "by using the lecture method, related questions and answers: (1) early childhood understanding of the scope of the internet and the use of gadgets / smartphones, (2) early childhood understanding of content on social media and the impact that will be obtained, and (3) simulation / playing learning together. The students at the activity location were equipped with a number of important knowledge regarding the use and when is the right time to use a smartphone that is appropriate for their age background. Then, the content, information, and what impacts can be obtained by early childhood children due to excessive internet access were explained as clearly as possible by the facilitators because it departed from the finding that these children were quite fluent in accessing the Google website and several popular social media. everyday. Therefore, it is hoped that there will be complete cooperation from parents and schools to be able to accompany the growth and development of children at this young age, including as a creative and skilled digital generation.